2006
DOI: 10.1177/154405910608500610
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Apoptosis in Early Tooth Development Alters Tooth Shape and Size

Abstract: Apoptosis plays important roles in various stages of organogenesis. In this study, we hypothesized that apoptosis would play an important role in tooth morphogenesis. We examined the role of apoptosis in early tooth development by using a caspase inhibitor, z-VAD-fmk, concomitant with in vitro organ culture and tooth germ transplantation into the kidney capsule. Inhibition of apoptosis at the early cap stage did not disrupt the cell proliferation level when compared with controls. However, the macroscopic morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 17 publications
0
28
0
2
Order By: Relevance
“…4). One means to achieve a size increase in teeth in mammals 33 is the suppression of apoptosis during early development (that is, suppressing p21, a cyclindependent kinase inhibitor), a mechanism associated with pathological macrodontia (anomalous enlargement of teeth). However, differences in apopotosis between reptile and mammal teeth are known, with apoptosis affecting the stellate reticulum in the former but occurring at the inner enamel epithelia in the latter 28 .…”
Section: Discussionmentioning
confidence: 99%
“…4). One means to achieve a size increase in teeth in mammals 33 is the suppression of apoptosis during early development (that is, suppressing p21, a cyclindependent kinase inhibitor), a mechanism associated with pathological macrodontia (anomalous enlargement of teeth). However, differences in apopotosis between reptile and mammal teeth are known, with apoptosis affecting the stellate reticulum in the former but occurring at the inner enamel epithelia in the latter 28 .…”
Section: Discussionmentioning
confidence: 99%
“…During odontogenesis, apoptosis regulates the cell number by eliminating cells that have already achieved their genetic program, thus controlling the pattern, shape and size of the teeth [7,8,24]. This control of patterns and shapes is manifested in the evolutionary diversity of mammalian tooth shapes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that apoptosis plays a key role in tooth shape and size [7][8][9][10]. Apoptosis is also involved in tooth anomalies associated with cleft lip and palate [11].…”
Section: Introductionmentioning
confidence: 99%
“…According to these results, the role of apoptosis here would be just a mechanism to scavenge the terminated cells rather than terminating the signaling role of the enamel knots. In contrast, Kim et al (2006) demonstrated that the tooth shape was altered when they treated explants cultures with the same inhibitor at the early cap stage. The control teeth showed proper crown formation, with six cusps; however, treated teeth displayed a shorter crown height and a longer mesiodistal diameter; moreover, in dose-dependent manner (25M, 50M, and 25M, and 100M inhibitor).…”
Section: Caspasesmentioning
confidence: 96%
“…Defects in apoptosis and/or in removal of ectopic tooth germs, may also play a role in determining the number of teeth, leading to the formation of supernumerary tooth formation, or influencing the ultimate size of a tooth. As such, apoptosis seems an attractive candidate factor for macrodontia (Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%